Morular Metaplasia of the Endometrium: A Case Report and Literature Review: Care Pathways based on Molecular Biology - Kotigala, Dhanushka SK; Adedipe, Tolu O (Clinical Journal of Obstetrics and Gynecology, 2024)
Background: Endometrial morular metaplasia, a clinical conundrum from a diagnostic and management angle given its rarity and low oncogenic potential, has been linked to endometrial hyperplasia and carcinoma. Case report: A 77-year-old woman with no significant past medical history, was found to have an asymptomatic thickened endometrium on pelvic imaging, after presenting with lower abdominal pain, 3yrs ago. Diagnostic hysteroscopy identified an endometrial polyp within a pyometra. Histopathology showed focal complex endometrial hyperplasia without atypia with superimposed morular metaplasia(EMM) with a negative microbiology assay. Following conservative management with multidisciplinary team(MDT) overview, as-per patient choice with 6-monthly follow-up hysteroscopy, endometrial biopsies and a short use of the Mirena® Intrauterine system (discontinued following poor tolerance), histopathology shows resolved hyperplasia with persistent EMM. Due to persistent disease, a hysterectomy is under consideration. Discussion: Current evidence suggests that a sub-type of EMM, a likely histological manifestation of beta-catenin (CTNNB1) gene mutation: could be a precursor of endometrial hyperplasia and low-grade endometrioid-endometrial carcinoma sub-type. Though low-grade in nature, the increased recurrence risk raises significant concerns. Prognostication following gene mutation identification can help with management options which include conservative, hormonal therapy with adjunct repeat endometrial sampling: or hysterectomy. The optimal frequency of endometrial sampling when uterine-sparing, is unclear, leading to a management conundrum, whilst persistent disease may require a hysterectomy.. Conclusion: Management of endometrial morular metaplasia can be difficult but must reflect the woman’s choice with a MDT-overview. Immuno-histochemical tools utilizing new molecular biological advances, can simplify the diagnostic and prognostication processes, aiding clinical management.